Assessment of salivary gland function after 177Lu-PSMA radioligand therapy: Current concepts in imaging and management - Sonia Mahajan; Ravinder K. Grewal; Kent P. Friedman; Heiko Schöder; Neeta Pandit-Taskar (Translational Oncology, 2022)
Prostate specific membrane antigen (PSMA) is a transmembrane protein that is highly expressed on prostate epithelial cells and is strongly upregulated in prostate cancer. Radioligand therapy using beta-emitting Lutetium-177 (177Lu)-labeled-PSMA-617, a radiolabeled small molecule, has gained attention as a novel targeted therapy for metastatic prostate cancer, given its high affinity and long tumor retention, and rapid blood pool clearance. In March 2022, the United States Food and Drug administration has granted approval to the targeted 177Lu-PSMA-617 therapy for treatment of patients with PSMA-positive metastatic castration resistant prostate cancer, who have been previously treated with an androgen-receptor pathway inhibitor and taxane-based chemotherapy. Studies have demonstrated the adverse effects of this treatment, mainly encountered due to radiation exposure to non-target tissues. Salivary glands show high PSMA-ligand uptake and receive increased radiation dose secondary to accumulation of 177Lu-PSMA-617. This predisposes the glands to radiation-mediated toxicity. The exact mechanism, scope and severity of radiation-mediated salivary gland toxicity are not well understood, however, the strategies for its prevention and treatment are under evaluation. This review will focus on the current knowledge about salivary gland impairment post 177Lu labeled PSMA-based radioligand therapies, diagnostic methodologies, and imaging with emphasis on salivary gland scintigraphy. The preventive strategies and known treatment options would also be briefly highlighted.